Antagonistic activity of lipopeptide-biosurfactant producing Bacillus subtilis AKP, against Colletotrichum capsici, the causal organism of anthracnose disease of chilli. (September 2021) - Kumar, Amrit; Rabha, Jintu; Jha, Dhruva Kumar
Abstract: Research for the development of biological control agents as an alternative to agrochemicals for controlling plant pathogens has gained considerable attention for the acquirement of agricultural sustainability. The present study reports a qualitative assessment of the potential of one promising antagonistic bacteria isolated from soil collected from Ultapani reserve forest, Assam, India, identified as Bacillus subtilis isolate AKP based on the morphological, biochemical, and molecular characteristic (NCBI GenBank Accession no. MW052029). The bacteria exhibited antagonistic activity against Chilli anthracnose fungus Colletotrichum capsici (61.5% growth inhibition in dual culture plate assay) which established the basis of further investigation. The strain AKP was found to exhibit biosurfactant producing ability with high emulsification index (83.1%) and surface tension reduction activity (83.8 to 21.9 ± 0.21). The crude extract from AKP strain also caused a significant reduction in disease incidence (anthracnose symptoms) by 16.66 ± 0.23% thus, providing good biocontrol efficiency against C. capsici based on in-vitro detached fruit assay. B. subtilis AKP showed the presence of surfactin ( srfAA ), iturin ( ituC ), and fengycin ( fenD ) antimicrobial biosynthetic genes in PCR assay. LC-MS analysis identified different homologues of surfactin, iturin, and fengycin lipopeptide biosurfactant from the methanolic fraction. Furthermore, the application of cell suspension-based B. subtilis also showed potentials for plant growth promotion both under in-vitro assays as well as in-vivo conditions in pot experiments. Our study revealed the potential of B. subtilis AKP in suppression of C. capsici as well as plant growth promotion which can be used on a commercial scale for the management of Anthracnose disease. Highlights: Isolation of antagonistic bacteria from microbiologically pristine soil environment. Antagonistic property of Bacillus subtilis AKP against Colletotrichum capsici (Causal organism of Anthracnose disease of chilli). Production of antifungal lipopeptide biosurfactant viz. surfactin, iturin, fengycin from Bacillus subtilis AKP. Bacillus subtilis AKP cell suspension (10 5 cells/ml) showed promising results in preventing anthracnose disease on chilli fruits under detach fruit assay. Application of Bacillus subtilis AKP cell suspension promoted plant growth in chilli.